2016
DOI: 10.1039/c6cp00385k
|View full text |Cite
|
Sign up to set email alerts
|

Novel scroll peapod produced by spontaneous scrolling of graphene onto fullerene string

Abstract: Novel scroll peapods are fabricated simply by utilizing the spontaneous scrolling mechanism of graphene onto fullerene string. The basic interaction between the graphene and the fullerene string is investigated, and the mechanism of the formation of the scroll peapod is explained in particular. The formation of the scroll peapod and its formation time are influenced by the combined effects of fullerene number, diameter and graphene size. It is also worth noting that narrow graphene nanoribbon wrapped onto a C7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…To study the self-assembly of the GNR structure immersed in water under an applied rotating E-field into a nanoscroll, we adopted the MD simulation approach. The MD approach is a popular technique for studying GNR-based systems. ,,,, We used the GPU-accelerated-GROMACS 5.1.5 package as the computational platform, wherein the carbon atoms were modeled as uncharged Lennard-Jones (LJ) particles and the optimized potentials for liquid simulations all atom (OPLS-AA) force field were implemented. Bonded interaction between carbon–carbon atoms was accounted for by a Morse bond potential for bond stretching, a harmonic cosine potential for bending and a 2-fold cosine potential for torsion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the self-assembly of the GNR structure immersed in water under an applied rotating E-field into a nanoscroll, we adopted the MD simulation approach. The MD approach is a popular technique for studying GNR-based systems. ,,,, We used the GPU-accelerated-GROMACS 5.1.5 package as the computational platform, wherein the carbon atoms were modeled as uncharged Lennard-Jones (LJ) particles and the optimized potentials for liquid simulations all atom (OPLS-AA) force field were implemented. Bonded interaction between carbon–carbon atoms was accounted for by a Morse bond potential for bond stretching, a harmonic cosine potential for bending and a 2-fold cosine potential for torsion.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there exists a trade-off between high quality and large quantity in the fabrication methods of GNSs that have been reported so far. More recently, theoretical , as well as experimental , works have proposed a purely physical route activated by nanotemplates such as water nanodroplets, single or multiwalled CNTs, diamond-like carbon nanoparticle, fullerene, Si nanowire, and metal nanoparticles to induce the self-assembly of graphene into hybrid core/shell composite structures. The common reason cited to explain the self-assembly is the van der Waals (vdW) interaction between nanotemplate and graphene that induces the encapsulation of the graphene nanoribbon (GNR) onto the template, resulting in the formation of a more stable hybrid structure than the individual ones.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-fullerenebased nanocomposite holds great promise for potential applications in different fields such as nano-electronics, optoelectronics, lasers, nano-mechanics, energy storage, energy conversion, spintronics, catalysis, sensors, cancer therapy and medical biology [23][24][25][26][27][28][29][30]. In the literature some molecular dynamics (MD) and density functional theory (DFT) based simulation studies on the interactions between graphene and fullerene and 2D materials have been reported [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations have been performed to study the charge transfer, electronic, magnetic and structural characteristics of various graphene-fullerene nanohybrid structures in the literature [41][42][43][44][45][46]. In the literature [31][32][33][34][35][36][37][38][39][40], MD simulation technique has been employed to study the motion of single fullerene on graphene sheet; structure of sandwiched fullerene molecules between layers of graphene; self-assembly of fullerene over graphene/carbon-based 2D materials; construction of nanoporous graphene with fullerene; molecular self-assembly over black phosphorene. Mukhopadhyay et al [40] have reported the minimum cytotoxicity of novel biocompatible 2D material based on carbon (C 2 N) from their MD simulation studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation